Red Blood Cell Distribution Width/Hematocrit Ratio: A New Predictor of 28 Days All-Cause Mortality of AECOPD Patients in ICU - Long Z; Zeng Q; Ou Y; Liu Y; Hu J; Wang Y; Wang Y (International Journal of COPD)
Zhiwei Long,1,2,* Qiyuan Zeng,2,* Yonger Ou,1,* Yuelin Liu,2,3 Jieying Hu,1 Ya Wang,1,3 Yan Wang1 1State Key Laboratory of Respiratory Disease, National Clinical Research Center for Respiratory Disease, Guangzhou Institute of Respiratory Health, The First Affiliated Hospital of Guangzhou Medical University, Guangzhou, People’s Republic of China; 2Department of Clinical Medicine, Guangzhou Medical University, Guangzhou, People’s Republic of China; 3Department of Critical Care Medicine, the First Affiliated Hospital of Guangzhou Medical University; Guangzhou Institute of Respiratory and Health; Medical Center for Respiratory Medicine; State Key Laboratory of Respiratory Disease, Guangzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yan Wang; Ya Wang, Email 345406739@qq.com; wangya811710@163.comPurpose: Elevated red blood cell distribution width (RDW) and decreased hematocrit (HCT) levels are associated with poor prognosis in chronic obstructive pulmonary disease (COPD) patients, but their significance in intensive care unit (ICU) patients with acute exacerbation of COPD (AECOPD) remains uncertain. The RDW/HCT ratio may offer a more comprehensive assessment compared to individual markers, potentially enhancing prognostic accuracy. Furthermore, the utility of RDW/HCT in improving traditional ICU scoring systems remains unexplored.Patients and Methods: The optimal RDW/HCT ratio cutoff was identified via ROC curve analysis, guiding classification into high and low ratio groups. Univariate and multivariate logistic regression analyses, Kaplan-Meier survival curves, and propensity score matching (PSM) were performed to evaluate the association between RDW/HCT ratio and 28-day all-cause mortality. The predictive value of RDW/HCT ratio compared to traditional ICU scoring systems was assessed using the area under the curve (AUC). Additionally, the eICU database was utilized to validate the robustness of the association between RDW/HCT and mortality in patients with AECOPD.Results: 624 patients were included, with 361 in the low RDW/HCT ratio group and 263 in the high ratio group. PSM yielded 145 matched pairs of patients with balanced baseline characteristics. Multivariate logistic regression analysis revealed that patients with RDW/HCT ratio ≥ 0.473 had significantly higher 28-day all-cause mortality compared to those with RDW/HCT ratio < 0.473 (p < 0.001). Combining RDW/HCT ratio with SOFA score improved the diagnostic accuracy significantly (p=0.029).Conclusion: The RDW/HCT ratio is an independent predictor of 28-day all-cause mortality in AECOPD patients in the ICU. It can be used for a preliminary assessment before a systematic evaluation of the patient, indicating its potential value in early assessment of disease severity. In a comprehensive evaluation, combining the RDW/HCT ratio with the SOFA score can further enhance predictive accuracy.Keywords: red blood cell distribution width, hematocrit, chronic obstructive pulmonary disease, intensive care unit, prognosis